Modelling and performance analysis of a new concept of integral collector storage (ICS) with phase change material. (1st May 2019) - Bilardo, Matteo; Fraisse, Gilles; Pailha, Mickael; Fabrizio, Enrico
Highlights: Modelling of an integral collector storage with phase change material. Model validation by means of experimental data. Yearly domestic hot water production simulation and global performance evaluation. Abstract: Solar Domestic Hot Water (SDHW) systems represent a constantly evolving technology in today's applications. With the new directives promoted by the European Union the renewable energy share produced in buildings will tend to increase further. Research on how to increase the efficiency of the thermal production from renewable energy are therefore of the foremost importance. This study aims to investigate the energy performance of an integral collector storage (ICS) prototype for DHW production. This ICS represents a new concept technology, integrating inside the same device a flat plate absorber and a storage section with phase change material (PCM) connected by heat pipes filled with methanol. An objective of this study was to investigate a possible alternative to conventional solar systems, with the aim of reducing investment costs and improving system reliability without compromising energy performance. The energy assessment was carried out using a numerical model in the Engineering Equation Solver (EES) environment, following an electrical analogy scheme. After a validation process by means of experimental data, a yearly simulation was launched in order to estimate the productivity and the solar fraction of the prototype. The results obtained allowed a global energy evaluation and a comparison with similar systems and to identify the pros and cons of this new technology.